THE USE OF ROMIPLOSTIM IN AN INFANT - Fatma Burçin KURTİPEK (Elsevier, 2021)
Case report: Immune thrombocytopenia (ITP) is the most common platelet disorder in children, peaking between the ages of 1-7.The first line therapy consists of intravenous immunoglobulin, anti-D immunoglobulin or corticosteroids. Second-line treatment options are immunosuppressive therapy, Rituximab.Thrombopoietin receptor agonists are used, which increase platelet production in the bone marrow. Our case report on a child with refractory chronic ITP, who failed the first and second line therapy.